Estimativa do balanço de energia a partir de medidas de protótipo de estação micrometeorológica - Silva Filho, Armando da (2015)
The conversion of large areas of Cerrado for agronomic crops and in urban areas modifies the microclimate, can be measured by the energy balance. However, the micrometeorological equipment have a high cost. Thus, this research aims to assess the development of a micrometeorological station capable of measuring the energy balance by Bowen ratio method in an area of sugar cane and in an urban area in the municipality of Barra do Bugres, Mato Grosso. In this work were developed balance radiometers, pyranometers, heat meter in the soil and termohigrômetros. These sensors we reset for calibration in conditions similar to commercial sensors, and then installed on a mast located in an area of sugar cane and urban. The energy balance was estimated by the Bowen ratio method. The pyranometer of correlations, balance radiometer, air temperature, and relative humidity, were greater than R2=0.98 and heat meter in the soil R2= 0.90. The net radiation was used primarily for the latent heat flux, 56.7% and 43.8%, followed by the sensible heat flux, 39.6% and 25.6%, and soil, 3.6% and 30.5% in the area of sugar cane and urban, respectively.